Novel Markers in Pediatric Acute Lymphoid Leukemia: The Role of ADAM6 in B Cell Leukemia - Alsuwaidi, Laila; Hachim, Mahmood; Senok, Abiola (Frontiers in Cell and Developmental Biology, 2021)
Abstract Background: The extensive genetic heterogeneity found in the B cell precursor acute lymphoblastic leukemia (BCP-ALL) subtype of childhood ALL represents a potential repository of biomarkers. To explore this potential, we have carried out in silico analysis of publicly available ALL datasets to identify genetic biomarkers for childhood BCP-ALL which could be used either individually or in combination as markers for early detection, risk stratification, and prognosis. Methods: To explore novel genes that show promising clinical and molecular signatures, we examined the cBiorpotal online tool for publicly available datasets on lymphoid cancers. Three studies on lymphoblastic and lymphoid leukemia with 1706 patients and 2144 samples of which were identified. To decrease heterogeneity, only the 1978 samples identified as B-Lymphoblastic Leukemia/Lymphoma samples were selected for further analysis. Chromosomal changes were assessed to determine novel genomic loci for the leukemia of lymphoid origin was identifiable. The cBioportal tool was used for the analysis of clinical and molecular profiles while the miRDB online database for miRNA target prediction and functional annotations was used for transcriptomic analysis. Results: Findings showed that ADAM6 gene homozygous deletions (HOM:DEL) were present in 25% of the patients and were associated with poor 10 years of overall patients’ survival. Moreover, patients with ADAM6 HOM:DEL showed a distinguished clinical and molecular profile with higher bone marrow and Central Nervous System (CNS) sites of relapse. In addition, ADAM6 HOM:DEL was significantly associated with unique microRNAs gene expression patterns. Conclusions: ADAM6 has the potential to be a novel biomarker for the development and progress of BCP- ALL.